STEM EDUCATION IN PRIMARY SCHOOL - Nilufar Otojanova (Modern American Journals, 2025)
The article explores the conceptual and practical foundations of STEM education as a key pedagogical innovation of the 21st century, emphasizing its role in developing creative, adaptable, and technologically competent specialists. It examines the global evolution of STEM and STEAM education, integrating science, technology, engineering, and mathematics with arts, humanities, and social sciences to foster critical thinking, problem-solving, and collaboration skills among learners. The study highlights the significance of engineering design, interdisciplinary learning, and practice-oriented approaches that connect education with professional development. Attention is given to the implementation of STEM education initiatives in Uzbekistan in accordance with recent presidential decrees aimed at modernizing school education, expanding extracurricular activities, and promoting scientific and technical creativity. The article also reviews international research on STEM trends, the demand for STEM-related professions, and the use of digital tools, robotics, and augmented reality technologies in education. It concludes that STEM education is essential for preparing a new generation capable of meeting the challenges of rapid technological change and global competition.
Keywords: STEM education, innovative pedagogy, interdisciplinary learning, engineering design, digital technologies, creativity, critical thinking, educational innovation, Uzbekistan education reform, 21st century skills.